Relationship between physical exercise, mediating variables and smartphone addiction in students: Narrative review: Relación entre ejercicio físico, variables mediadoras y adicción al smartphone en estudiantes: revisión narrativa (Papeles, 2023)
Addiction to smartphones is associated with negative effects on psychophysical health and social well-being. Physical activity and addiction to smartphones are considered as two independent but interrelated variables in terms of health. Its possible connection has been explored by proposing how physical activity, physical exercise or participation in sports can be used as an intervention strategy to treat this addiction. The objective is to carry out a narrative review of the literature on the relationships between physical activity or participation in sports, mediating variables and addiction to smartphones in the student population. Methodology: A search was carried out in the main research databases: Web of Science and Scopus, to find the relevant literature on the relationships between addiction to smartphone use and the practice of physical exercise. Results and discussion: The results suggest that as smartphone addiction increases, the level of physical activity in students decreases. The results on physical inactivity, mediating variables, addictions, perceptions and psychological abilities are discussed, and guidelines are proposed to prevent addiction to smartphones in adolescent students. Conclusions: Smartphone addiction can be reduced by increasing participation in sports and physical activity/exercise among students. Educational institutions can use sport and exercise as an intervention strategy to deal with addiction to smartphones in the student population.
Keywords: physical activity; exercise; smartphone; addiction; education; students